A simple formula for time-dependent seismic reliability assessment of aging structures - ICASP14; Wang, Cao; Teh, Lip (My University, 2023)
The capacity deterioration of structures over time may impair their seismic structural reliability significantly, and thus should be taken into account when assessing their seismic performance. In this paper, a simple formula is proposed for time-dependent seismic reliability analysis of deteriorating structures. The capacity deterioration on the temporal scale is captured by the generalized capacity and deterioration function, and the Fréchet distribution is used to describe the probabilistic behaviour of the peak ground acceleration. The proposed formula is based on some minor assumptions on the probability models of the deterioration process and of the seismic hazard, and does not involve the computation of integrals, which is beneficial for use in practical engineering. A numerical example is presented to demonstrate the accuracy and applicability of the proposed reliability analysis method.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED